2004
DOI: 10.1097/00001756-200411150-00021
|View full text |Cite
|
Sign up to set email alerts
|

Reduced electrodermal response to errors predicts poor sustained attention performance in attention deficit hyperactivity disorder

Abstract: Research into ADHD has indicated abnormalities in electrodermal system activity (EDA) and separately, deficits in sustained attention. Here we asked for the first time whether reduced EDA in ADHD was consequential for the attention problems associated with this disorder. On a sustained attention task ADHD participants had higher overall error rates and exhibited a marked decrease in skin conductance responses (SCRs) to errors, relative to control children. Further, sustained attention errors were predicted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 21 publications
3
43
0
1
Order By: Relevance
“…SC responses have been associated with affective processing of stimuli, such as discriminating between good and bad outcomes (Damasio 1996). O'Connell et al (2004) reported smaller SC responses to errors in children with ADHD than in controls. Since children with ADHD demonstrated intact post-error response slowing (an indicator of error detection) in that study, reduced SC responses were interpreted as evidence for a decreased awareness of the significance of errors.…”
Section: Psychophysiologymentioning
confidence: 99%
“…SC responses have been associated with affective processing of stimuli, such as discriminating between good and bad outcomes (Damasio 1996). O'Connell et al (2004) reported smaller SC responses to errors in children with ADHD than in controls. Since children with ADHD demonstrated intact post-error response slowing (an indicator of error detection) in that study, reduced SC responses were interpreted as evidence for a decreased awareness of the significance of errors.…”
Section: Psychophysiologymentioning
confidence: 99%
“…Sympathetic activity is linked to both emotional and cognitive states, and electrodermal activity is widely used as a sensitive index of bodily arousal related to emotion and attention [30] . The GSR [28] has been shown to be sensitive to changes in sustained attention [31] , with reduced electrodermal response to errors predicting poor sustained attention performance.…”
Section: Introductionmentioning
confidence: 99%
“…The Sustained Attention to Response Task (SART) [33] was included as a measure of sustained attention, as the simplicity of this task tends to encourage a routine response set, placing heavy demands on the individual's ability to endogenously maintain the overall goal of withholding to the no-go target [31] . The sensitivity of the SART for indexing self-reports of everyday attentional failures has been documented [33] , as has its activation of the right-hemisphere alertness network [34] .…”
Section: Introductionmentioning
confidence: 99%
“…The present study attempts to better understand the difficulty Rett children have with this aspect of attention and identify factors influencing it. Sustained attention, which is thought to involve top-down connectivity extending from the anterior attention system, particularly prefrontal and parietal regions in the right hemisphere, right down into V1 (Grahn & Manly, 2012;Sarter, Givens, & Bruno, 2001;Silver, Ress, & Heeger, 2007), has repeatedly been found to be compromised across a wide range of neurological and psychiatric disorders, e.g., ADHD, autism, bipolar disorder and Fragile X (Cornish, Scerif, & Karmiloff-Smith, 2007;Cornish, Turk, & Levitas, 2007;Fortenbaugh et al, 2015;O'Connell, Bellgrove, Dockree, & Robertson, 2004) While sustained attention is often tested in adults with the continuous performance test, the verbal instructions and motoric requirements preclude using this task in children with RTT.…”
mentioning
confidence: 99%